ANALISIS KINERJA USAHA PENGGILINGAN PADI DI PABRIK PENGGILINGAN PADI MILA KARMILA MENGGUNAKAN METODE BALANCED SCORECARD - Salim; M. Fuadi, Mamik; Sukandi, Andi (LPPM Sekolah Tinggi Teknologi Cipasung, 2024)
The Mila Karmila Rice Milling Factory is one of the rice milling factories in the Leuwisari sub-district, Tasikmalaya district. This factory has been established since 2011. With weekly production reaching 16 tons. The Mila Karmila factory also has its own market which orders every week. With this production amount, it turns out that the Mila Karmila Milling Factory is still not optimal, especially in terms of profits. There are many unexpected costs, which cause waste in the production process. The aim of this research is to determine the business performance of the Mila Karmila rice milling factory and provide suggestions for how to evaluate its business performance. The method used in this research is the Balanced Scorecard method. The results of the research are an explanation of the current business performance of the Mila Karmila rice milling factory and suggestions for how to evaluate it in the future.